First-principles investigations on the thermal transport and thermoelectric properties of anti-perovskite M3OI and M4OI2 (M = K, Rb) - Xiao, Hong; Hu, Tao; Zhou, Ping; Li, Dengfeng (Frontiers in Physics, 2025)
The thermal transport and thermoelectric properties of anti-perovskite M3IO and M4I2O (M = K, Rb) were investigated using first-principles calculations combined with solution of the Boltzmann transport equation. The two-phonon scattering channel was also considered. These structures formed M6O octahedra, accompanied by a rattling motion of the O atoms. They exhibit ultra-low lattice thermal conductivity, ranging from 0.30 to 0.89 W m-1 K−1 at room temperature. M4I2O demonstrates strong anisotropic thermal transport due to weaker bonding interactions along the zz direction, while M3IO shows isotropic thermal conductivity. Specifically, Rb4OI2 has the lowest lattice thermal conductivity of 0.47 W m-1 K−1 along the xx direction and 0.30 W m-1 K−1 along the zz direction. Additionally, M3IO possesses low lattice thermal conductivity of 0.52 W m-1K−1, attributed to the softening behavior of the TA branch at the M and R points. The electronic structure of M3IO and M4OI2 reveals a multi-valley phenomenon in the valence band, resulting in a large Seebeck coefficient under p-type doping. Our results indicate maximum thermoelectric figure of merit (ZT) values of 1.91 for p-type Rb3OI, and 1.41 for p-type Rb4OI2 along the zz direction at 900 K. Rb3OI and Rb4OI2 were proposed as potential p-type thermoelectric materials.